2013
DOI: 10.1136/thoraxjnl-2013-203485
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and impact of Xpert MTB/RIF for the diagnosis of smear-negative or sputum-scarce tuberculosis using bronchoalveolar lavage fluid

Abstract: Rationale The accuracy and impact of new tuberculosis (TB) tests, such as Xpert MTB/RIF, when performed on bronchoalveolar lavage fluid (BALF) obtained from patients with sputum-scarce or smear-negative TB is unclear. Methods South African patients with suspected pulmonary TB (n=160) who were sputum-scarce or smear-negative underwent bronchoscopy. MTB/RIF was performed on uncentrifuged BALF (1 ml) and/or a resuspended pellet of centrifuged BALF (~10 ml). Time to TB detection and anti-TB treatment initiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
98
7
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(115 citation statements)
references
References 29 publications
8
98
7
2
Order By: Relevance
“…[2] We included a small proportion of cases (14/83) in which diagnoses were never microbiologically confirmed (diagnosed on clinical and radiological criteria). Although this is not an infrequent practice in studies from high endemic areas, [17] it may have introduced some bias.…”
Section: Discussionmentioning
confidence: 99%
“…[2] We included a small proportion of cases (14/83) in which diagnoses were never microbiologically confirmed (diagnosed on clinical and radiological criteria). Although this is not an infrequent practice in studies from high endemic areas, [17] it may have introduced some bias.…”
Section: Discussionmentioning
confidence: 99%
“…15 Theron et al In their study of 154 patients in a South-African single-centre study analysed the BAL samples in which sensitivity and specificity values compared to the culture were 92.6% and 96.0% for the Xpert® MTB/RIF assay, and 57.7% and 99.3% for SM, respectively. 16 Le Palud et al concluded that as compared to culture, sensitivity and specificity values were 80.0% and 98.6% for the Xpert® MTB/RIF assay. 12 …”
Section: Techniquesmentioning
confidence: 99%
“…One obvious advantage of breath analysis over sputum tests is the simplicity of obtaining the sample; this is in contrast to the difficulties in obtaining sputum both in children and HIV patients [5,6]. The lack of confounding by HIV is another clear advantage over the existing TB diagnostic tests, which exhibit up to 43% misclassification in HIV-TB co-infected persons [14].…”
mentioning
confidence: 99%
“…In the present study, we used NAAT as a complementary diagnostic test to verify a true-negative result in subjects who were found to be negative with a sputum test [6], and were known to have relatively low sensitivity, yet a very high (,100%) specificity [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation